Metastatic sigmoid adenocarcinoma to the larynx: A case report and updated literature review - Adham A. Aljariri (14777449) (2023)
Metastatic laryngeal cancer is a rare entity, usually indicating an advanced disease once discovered. In this report, we are describing a case of a 60‐year‐old male patient with stage IV colorectal cancer (CRC), who presented to our clinic with dysphonia; further workups showed metastatic CRC. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/ccr3.6942